A validation of the short-form classroom community scale for undergraduate mathematics and statistics students - Tackett, Maria; Viel, Shira; Manturuk, Kim (Journal of University Teaching and Learning Practice, 2023)
This study examines Cho & Demmans Epp’s short-form adaptation of Rovai’s well-known Classroom Community Scale (CCS-SF) as a measure of classroom community among introductory undergraduate math and statistics students. A series of statistical analyses were conducted to investigate the validity of the CCS-SF for this new population. Data were collected from 351 students enrolled in 21 online classes, offered for credit in Fall 2020 and Spring 2021 at a private university in the United States. Further confirmatory analysis was conducted with data from 128 undergraduates enrolled in 13 in-person and hybrid classes, offered for credit in Fall 2021 at the same institution. Following Rovai’s original 20-item CCS, the 8-item CCS-SF yields two interpretable factors, connectedness and learning. This study confirms the two-factor structure of the CCS-SF, and concludes that it is a valid measure of classroom community among undergraduate students enrolled in remote, hybrid, and in-person introductory mathematics and statistics courses.